Nurses’ Perceptions About Conflict Management Strategy of Head Nurse - Rai Rosita Candra Dewi; Ni Putu Emy Darma Yanti; Indah Mei Rahajeng; Komang Menik Sri Krisnawati (KHD-Production, 2022)
Conflict is one of the factors that affect the performance of nurses. Nurse’s conflict management is closely related to the role of leaders in creating a conducive and productive work environment. The purpose of this study was to describe the perception of implementing nurses on the management of ward head conflict in a hospital in Bali. This research is a quantitative descriptive study with a cross sectional approach. The respondents involved were 71 nurses using purposive sampling technique. Collecting data using a questionnaire about conflict management that has been valid and reliable. The results of the research on the perception of implementing nurse on the conflict management of head nurse from dominating strategy were the “Not Good” category (56.95%), the collaboration strategy was “Good” (85.75%), the avoidance strategy was “Not Good” (44%), the accommodate “Good” (82%), and the compromise strategy “Good” (87%). The majority of implementing nurses perceive that the head nurse uses a compromise strategy in managing conflict in their work area, and the least perceived is that the leader uses a conflict avoidance management strategy. The head nurse is expected to be able to use appropriate conflict management strategies to resolve conflicts in his scope of work, because in general all strategies have their respective advantages and disadvantages to overcome a problem.